Human genome-wide measurement of drug-responsive regulatory activity. Issue 1 (December 2018) - Johnson, Graham; Barrera, Alejandro; McDowell, Ian; D'Ippolito, Anthony; Majoros, William; Vockley, Christopher; Wang, Xingyan; Allen, Andrew; Reddy, Timothy
Abstract Environmental stimuli commonly act via changes in gene regulation. Human-genome-scale assays to measure such responses are indirect or require knowledge of the transcription factors (TFs) involved. Here, we present the use of human genome-wide high-throughput reporter assays to measure environmentally-responsive regulatory element activity. We focus on responses to glucocorticoids (GCs), an important class of pharmaceuticals and a paradigmatic genomic response model. We assay GC-responsive regulatory activity across >108 unique DNA fragments, covering the human genome at >50×. Those assays directly detected thousands of GC-responsive regulatory elements genome-wide. We then validate those findings with measurements of transcription factor occupancy, histone modifications, chromatin accessibility, and gene expression. We also detect allele-specific environmental responses. Notably, the assays did not require knowledge of GC response mechanisms. Thus, this technology can be used to agnostically quantify genomic responses for which the underlying mechanism remains unknown. Quantification of genomic responses to environmental stimuli by current genome-scale assays is limited to indirect measurements or requires knowledge of the transcription factors involved. Here, the authors use genome-wide high-throughput reporter assays to agnostically map enhancer activity in response to glucocorticoid treatment across the human genome.